A Comprehensive Islamic Management Theory Theory (I) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
-A good head and a good heart are always a formidable combinationllWhen discussing management, we have to start with a historical perspective that enables us to understandits evolution as:1) It clarifies our view of the present,2) It allows us to explain the way things are,3) It instils a sense of causation, and4) It underlines the importance of interpretation in social science.The history of management thought starts from a search for a universal theory that fits all purposes, allsocieties, all cultures and all fields. Yet we see no single theory is accepted today. Instead we have theoriesdevised and developed at different times with applications to different aspects of the management role.In the East, there are theories that have roots to Ancient Egypt or China; while the participation of Arab andIslamic scholars was very limited, due to the fact that their civilization was targeted by others, especially theCrusaders or the Mongols, who destroyed their Cultures in their cradles (Baghdad or Damascus), when theyinvaded their homelands and killed their scholars. Consequently, their priorities were mixed up and they became retroactive instead of being proactive; except for three recent endeavours:r 1) Dr. Tariq Al-Sweidan in Kuwait,2) Prof. Abdul Aziz Abu Nab‘a, in Palestine, and3) Dr Abdul Muti M. Assaf in JordanAgain those theorists undermined the Ethical, Belief and Cultural/Behavioral straightness, but in some waytackled the surrounding environments that shape the organizational culture and the leaders as well.None of them could be categorized as to serve andface challenged for all the recent purposesI presume, that my theory, The Comprehensive Islamic Management Theory (I) will fit. Let us try it.